Community Empowerment in the Utilization of Beronok to Improve Nutritional Quality and Lifestyle in Meranti Regency - Rahmad, Hari Adi; Azri, Harizqi; Rahmat, Wahyudi (Bhandar: Harvesting Community Service in Asia, 2024)
The Meranti Regency is endowed with a rich biodiversity, including the sea cucumber, locally known as beronok, which has been recognized by the local community for its high nutritional value. This article explores community empowerment efforts aimed at utilizing beronok to enhance nutritional quality and overall well-being. With its rich content of protein, minerals, and other health benefits, beronok holds the potential to be developed into a valuable functional food source. Through educational programs and training, the community is encouraged to process and utilize beronok effectively to support food security and promote healthier lifestyles. This initiative not only aims to improve the nutritional intake of the local population but also to enhance their socio-economic status by creating new opportunities for livelihood through sustainable use of natural resources. By increasing community awareness and skills in processing beronok, the program seeks to foster a self-sufficient and health-conscious community. The study highlights the importance of integrating local resources into community development strategies to address nutritional challenges and improve living standards, thereby contributing to the overall resilience and sustainability of the region.